The Influence of Perceived Usefulness and Perceived Ease of Use on the Performance of State Financial Management (Study on the Work Unit of the Ministry of Education and Technology) - I Dewa Gede Sayang Adi Yadnya (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the effect of Perceived Usefulness and Perceived Ease of Use on the Performance of State Financial Management. The research approach used in this research is a quantitative approach. Quantitative research methods aim to test the established hypotheses. This type of research is causal effect research. Causal effect research is research that aims to determine the relationship or influence between two or more variables. The exact number of the population is not known. Respondents in this study were 100 people in the Higher Education Service Institution Work Unit (LLDIKTI) area 3 with respondents spread across Medan, Palembang, Bandung, Yogyakarta, Semarang, Surabaya, Denpasar, Makassar, Padang, Banjarmasin, Aceh, Jayapura and Gorontalo. The data in this study were obtained by distributing the G-Form questionnaire given to the WhatsApp group. The data analysis used a structural approach to the Equation Model (SEM) assisted by the smart PLS application. Based on the results of the tests carried out, it is known that perceived ease of use and usefulness have a significant positive effect on state financial management. The treasurer as the credit card holder can maintain his integrity in managing state finances so that he can maintain the performance of state financial management that has been achieved so far.